Crime survey for England and Wales, 1996-2020: secure access (Crime Survey for England and Wales, 2022)
The main CSEW 1996-2020 Secure Access dataset (SN 7280) includes: the adult and child data also held in the standard End User Licence (EUL) version; adult self-completion modules on drinking behaviour, drug use, stolen goods, children's self-completion modules and sexual identity and low-level geography variables formerly held under Special Licence access conditions (please note that not all modules occur for each year - see the survey year's documentation for details); hate crime variables HATEMT3A-HATEMT3I and HATEPS3A-HATEPS3I from the victim form; the interpersonal violence (IPV) data (comprising the modules on domestic violence, sexual victimisation and stalking)For the 11th edition (August 2021), data and documentation for the CSEW 2019-2020 were added to the study.